PROMOTION AND PROMOTION REVIEW IN CANADIAN UNIVERSITIES - Campbell, R. (Revue de droit de l'Université de Sherbrooke)

(untitled) (Revue de Droit de l’Université de Sherbrooke, 1985)
There is little question that with the very limited number of new appointments being made in Canadian colleges and universities during recent years, the focus of attention has shifted from tenure to promotion. Yet both these processes are extremely important but little understood. It is only when one is a candidate for either tenure or promotion that the issue is personalized and interest is aroused. Nevertheless, tenure and promotion criteria and procedures have been very much the focus of collective agreements and judicial proceedings.Provisions that deal with promotion in association and collective agreements between faculty and administrations have striking differences with respect to procedure. These provisions are tailored to ensure that the candidate is dealt with fairly. In most agreements, however, the criteria with respect to promotion are vague and little guidance is given with respect to the weight to be given to or the standard required for each criterion. One issue concerning procedure that has not been satisfactorialy considered by the courts is that of confidentiality. Arbitration boards are just starting to deal with the complexity of this issue.Promotion disputes can be resolved either by arbitration or the courts. The scope of review and remedial power of an arbitration board may be determined by the parties to the agreement. Most often the case is sent back for reconsideration, but the difflculty facing arbitration boards is the standard by which a decision must be reviewed.The Paine decision clearly signalled the court's willingness to review a case dealing with academic status. Several cases have followed in response to some of the questions left unanswered by Paine. It may be that the courts review will extend to matters purely concerned with position as in Scholdra. But, it is still not clear what the limits of judicially enforced fairness will ultimately be.Despite the focus that promotion may have in agreements and judicial proceedings, promotion must by carefully examined. This is particularly acute in terms of the purpose of promotion as a process of performance review.